Jo Spence e Hannah Wilke: narrativas da dor - Arcanjo, Kárita Gonzaga de Oliveira (2014)
This research aims to investigate the sick body and the pain representation by means of photography, considering its documentary and narrative elements. To that end we elected the photographic series The Picture of Health? (1982-1986) and Narratives of Disease (1990) by Jo Spence (1934-92) and Intra-Venus (1992-1993) by Hannah Wilke (1940-93), which focus on the cancer photographic documentation, taking into account their meanings as photographic narratives. In these series we have as interests the pathological pain of the sick and treated body and the image built from its appropriation by these artists. Basing on the study of self-portrait we discuss the relationship between pose and identity in the photographic image constitution as well as the concepts of photography-document proposed by André Rouillé and photographic narrative adopted by Susan e. Bell. Thus, we understand Jo Spence‘s and Hannah Wilke‘s narratives as potent instruments to face the pain, the silence and the stigma which the cancer patient is submitted, and still, a way for questioning the female image socially and culturally constructed.